2013
DOI: 10.1371/journal.pone.0066053
|View full text |Cite
|
Sign up to set email alerts
|

Early Root Herbivory Impairs Arbuscular Mycorrhizal Fungal Colonization and Shifts Defence Allocation in Establishing Plantago lanceolata

Abstract: Research into plant-mediated indirect interactions between arbuscular mycorrhizal (AM) fungi and insect herbivores has focussed on those between plant shoots and above-ground herbivores, despite the fact that only below-ground herbivores share the same part of the host plant as AM fungi. Using Plantago lanceolata L., we aimed to characterise how early root herbivory by the vine weevil (Otiorhynchus sulcatus F.) affected subsequent colonization by AM fungi (Glomus spp.) and determine how the two affected plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 59 publications
1
16
1
Order By: Relevance
“…The reduction of AG herbivore growth should be attributed to other potentially induced defense traits, lower foliar nutrient values or physical defenses, which directly reduced leaf consumption by these herbivores. A shift in the relative composition of defense compounds can also lead to significant responses of herbivores (Bennett et al 2013), although it was not found in the current study (chapter 3). Another major finding in this thesis is that I observed that induced defense by AG herbivory in plant foliage against later conspecifics was canceled out when the plant roots were also exposed to feeding by BG herbivores (Figure 2.3).…”
Section: Timing Of Attack By Aboveground and Belowground Herbivores Ocontrasting
confidence: 63%
See 3 more Smart Citations
“…The reduction of AG herbivore growth should be attributed to other potentially induced defense traits, lower foliar nutrient values or physical defenses, which directly reduced leaf consumption by these herbivores. A shift in the relative composition of defense compounds can also lead to significant responses of herbivores (Bennett et al 2013), although it was not found in the current study (chapter 3). Another major finding in this thesis is that I observed that induced defense by AG herbivory in plant foliage against later conspecifics was canceled out when the plant roots were also exposed to feeding by BG herbivores (Figure 2.3).…”
Section: Timing Of Attack By Aboveground and Belowground Herbivores Ocontrasting
confidence: 63%
“…Wireworms alone strongly reduced the levels of IGs in roots and increased the ratio of the more toxic compound catalpol relative to aucubin. The latter effect has been observed for other root herbivores as well (Bennett et al 2013). The reduction in root IG levels was initially counterbalanced by the increase in root IG levels caused by simultaneously introduced S. exigua.…”
Section: Arrival Sequence and Aboveground-belowground Interactionsmentioning
confidence: 59%
See 2 more Smart Citations
“…Because the commercial AMF mix that we used was purported to consist of four AMF species, the different effects of AMF availability on herbivore performance may be a function of differential colonization by AMF species under medium and high AMF availability. AMF species vary in their relative trading of nutrients (Lendenmann et al, 2011;Thonar et al, 2014;Argüello et al, 2016) and effects on plant phenotype (Gehring and Bennett, 2009;Bennett et al, 2013) which can alter herbivore performance (Roger et al, 2013;. However, cloning and sequencing of the AMF mix, and roots from milkweed plants grown under the same experimental conditions, with AMF-specific primers (Krüger et al, 2009) demonstrated that the AMF mix consisted only of F. mosseae (details in Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%